الطبيعة القانونية للسلطات الإدارية المستقلة في الجزائر والأنظمة المقارنة - بوطابت, كريمة (جامعة الوادي University of Eloued, 2019)
إن تحديد الطبيعة القانونية للسلطات الإدارية المستقلة قد عرفا جدلا واسع النطاق في الجزائر على غرار كل دول العالم ، ففي ظل التزام القضاء موقف الحياد تجاه هذه المسألة في جل الأحوال، نجد المشرع قد كيف بعض هذه الهيئات بصريح النص ، في حين بقي مترددا أو التزم الصمت في تكييف بعضها الآخر و هو مايعكس غياب رؤية متكاملة متجانسة وواضحة حول النظام القانوني لهذه الهيئات و إمكانية تشكيلها لفئة قانونية موحدة من عدمه. Abstract: Defining the legal of independent administrative authorities in Algeria as all over the world has been very controvertial.While the judiciary kept neutral almost in all cases,the Algerian legislature; however , has provided an explicit legal characterization in some cases and hesitated or did not intervene in many other ones.Thus, no integral ,homogenous and clear vision is provided over these institutions of having a uniform legal category.
The Légal Charactérization Of Independent Administrative Authorities In Algeria And The Comparative Systems
Keywords: السلطات الادارية المستقلة ؛ التكييف القانوني ؛ النظام القانوني ؛ المشرع الجزائري؛القضاء; Independent administrative authorities. Legal characterization; Légal System; Algerian Législature ; Judiciary